Active contours driven by novel fitting term for image segmentation. Issue 13 (1st June 2017) - Ni, Kang; Wu, Yiquan
Abstract : Active contour model driven by novel fitting term is proposed for image segmentation in this letter. The novel fitting term contains two parts: one is L 1 fitting term, which describes the change of energy between inside and outside the curve; another is the reciprocal cross‐entropy fitting term, which can compute the local energy of every point on the curve. The reciprocal cross‐entropy fitting term is more robust than L 1 fitting term when the regional grey scale fluctuates greatly, and the detail direction of the curve can be controlled better by it. Experiments on several synthetic and real images have shown that the proposed model achieves better segmentation results and efficiency than the other models; in addition, it is insensitive to different initial contours.